WESTERNIZATION (MODERNIZITON) MOBILITY FOR TRANSITION TO INFORMATION SOCIETY THE IMPORTANCE OF eLEARNING AND UDEEEWANA - Uğur DEMİRAY (International Journal of Eurasia Social Sciences, 2016)
As a result of improvements in computer and communication technologies, there has been a remarkable increase in new approaches, methods and techniques aiming to achieve more effective and efficient educational experiences. As today’s digital era highly requires limitless, rapid flow in sharing and obtaining the information, new ways of education generally provide opportunities like ‘education without time and place limitations’ Rapidly developments are gaining more attention on our planet and our daily life than ever before. We have newer and more complex questions as well as greater challenges and vast new opportunities. Today’s institutions, policy makers, scholars and students of traditional and distance education in higher education are different than the organizations and people in the 20th Century. This paper aims to review and discuss the approaches lead by worldwide experts who specialize in distance education. DE experts are share their findings and analysis of the current trends and implications for present and future policies. Moreover, these experts practice to catch the mobility of westernization and globalization through an efficient way for distance education in the world. This presentation is divided into three main structural sections according to the eLearning importance and being a functional UDEEEWANA creation: Westernization Mobility, for Information Society and Transition to Information Society